PENTINGNTA MODUL PEMBELAJARAN IPS BERBABASIS MODEL EXAMPLE NON EXAMPLE DI SEKOLAH DASAR - Feby Kurniawan; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Education is a person's process of developing an education system. In the learning process, the media has a function as a means of communication and must be used in every learning process. The purpose of writing this article is to inform about the importance of the Example non Example model-based social studies learning module in elementary schools, the benefits it generates especially in the development of cognitive abilities and the various ways that can be done in carrying out learning using Example non Example based Modules. The writing of this article uses a literature review approach using secondary data obtained from various research data. The results of the study found that in general the media used were learning modules because they were considered easier to use. Through the Example Non Example Model-based learning module students will find it easier to access everything related to learning material and will become a source of independent learning for students. Thus, the Example non Example-based learning module will be able to develop students' cognitive abilities to the fullest, especially in elementary school age students. Keywords: Development, Module, Example non-Example.